Enhanced liver regeneration following changes induced by hepatocyte-specific genetic ablation of integrin-linked kinase - Apte, Udayan (2009)
Following liver regeneration after partial hepatectomy, liver grows back precisely to its original mass and does not exceed it. The mechanism regulating this “hepatostat” is not clear and no exceptions have been found to date. While pathways initiating liver regeneration have been well studied, mechanisms involved in termination of liver regeneration are unclear. Here we report that Integrin Linked Kinase (ILK) (involved in transmission of the extracellular matrix (ECM) signaling via integrin receptors) and/or hepatic adaptations that ensue following ILK hepatocyte-targeted removal, are critical for proper termination of liver regeneration. Following partial hepatectomy (PHX), mice with a liver-specific ILK ablation (ILK-KO-Liver) demonstrate a termination defect resulting in 58% larger liver than their original pre-PHX mass. This increase in post-PHX liver mass is due to sustained cell proliferation driven in part by increased signaling through HGF/Met, and β-catenin pathway and Hippo Kinase pathways. The data indicate that ECM-mediated signaling via ILK is essential in proper termination of liver regeneration. This is the first evidence of a defect leading to impaired termination of regeneration and excessive accumulation of liver weight following partial hepatectomy.